PENENTANGAN KAUM MUDA MINANGKABAU TERHADAP BUDAYA MINANGKABAU DALAM CERPEN HARIAN KOMPAS [The Defense of Young Minangkabau on Minangkabau Culture in The Compass Short Story] - Jasril Piliang (TOTOBUANG, 2017)
The writing of literary works by authors from Minangkabau is dominated by the theme of youth resistance to Minangkabau culture supported by the Elder. Therefore, this article tried to discuss about young people's resistance to Minangkabau culture in the Kompas Daily short story. The research data was collected from four short stories by Minangkabau authors published by Kompas daily and analyzed using the theory of sociology of literature by using mimesis approach. This type of research was qualitative descriptive. Collecting and analyzing data were done simultaneously with reading-record-analysis technique, used content analysis method and heuristic and hermeneutic reading method. The findings of the study and discussion revealed that the short story of the Kompas Daily contained the resistance of Minangkabau youth which included resistance to the tradition of money pick-ups,  to the customary provisions that prohibit boys in Minangkabau occupied communal land, to mamak policies abusing inherited property, and  to the ban on marriage in the Minangkabau culture.Penulisan karya sastra oleh pengarang yang berasal dari Minangkabau didominasi oleh tema penentangan kaum muda terhadap budaya Minangkabau yang didukung oleh kaum tua. Oleh sebab itu, artikel ini mencoba melihat penentangan kaum muda terhadap budaya Minangkabau dalam cerpen Harian Kompas. Data penelitian dikumpulkan dari empat cerpen karya pengarang Minangkabau yang diterbitkan Harian Kompas dan dianalisis menggunakan teori sosiologi sastra dengan menggunakan pendekatan mimesis. Jenis penelitian ini adalah kualitatif deskripstif. Pengumpulan dan penganalisisan data dilakukan secara bersamaan dengan teknik baca-catat-analisis, menggunakan metode content analysis dan metode pembacaan heuristik dan hermeneutik. Temuan penelitian dan pembahasan mengungkapkan bahwa cerpen Harian Kompas memuat penentangan kaum muda Minangkabau yang meliputi penentangan terhadap tradisi uang jemputan, penentangan terhadap ketentuan adat yang melarang anak laki-laki di Minangkabau menempati tanah ulayat, penentangan terhadap kebijakan mamak yang menyalahgunakan harta pusaka, dan penentangan terhadap larangan pernikahan sesuku dalam budaya Minangkabau.